Multi-Departments to Cover the Whole Computational Discipline. - Segall, Mark (Communications of the ACM, 2010)
A letter to the editor is presented in response to the article "What Should We Teach New Software Developers? Why?" by Bjarne Stroustrup in the January 2010 issue.